A variational approach to the modelling of grooving in a three-dimensional setting. (1st May 2017) - Hackl, Klaus; Fischer, Franz Dieter; Svoboda, Jiri
Abstract: We present a theory of thermal grooving, i.e. surface motion due to surface diffusion, based solely on geometrical and energetic arguments and a variational approach involving a thermodynamic extremal principle. The theory is derived for a fully three-dimensional setting. All interface and contact conditions at junction lines and points of the material aggregate are derived rigorously and without ambiguity. A finite element implementation of the model is employed. Numerical examples are presented and compared with experimental results from the literature. Graphical abstract: Image 1